Carbon fiber reinforced composite material layup design optimization method and its application in automobile battery box - Dongzhen Lu; Shuai Zhang; Zhao Li; Jiufeng Chen; Feng Xiong; Yuzhuo Zhang; Jinlong Xiao (PLoS ONE, 2025)
In order to improve the lightweight level of new energy vehicle battery box assembly and its design efficiency and precision, a design scheme of sheet molding compound (SMC) composite box upper plate and carbon fiber composite lower box was proposed. Based on digital twin technology and combined with an improved particle swarm-bacterial foraging (PSO-BFO) algorithm, a fiber reinforced composite layup design and multi-level twin optimization method was proposed. The SMC composite material upper panel was designed and optimized by using the morphology optimization and size optimization methods. The carbon fiber composite material lower panel layup sequence was designed and optimized by using the constructed digital twin multi-level optimization method. Comparing the performance of the battery box assembly before and after optimization, the improvement rates of battery box assembly quality and first-order modal frequency were 40.63% and 33.34% respectively. The stress improvement rates under bumpy conditions, bumpy+braking conditions/bumping+turning conditions are 83.60%; 81.01%; 84.31% respectively, and the displacement improvement rates are 62.80%, 63.21%, and 63.14% respectively. Lightweight and performance improvement The effect is remarkable. The effectiveness of the battery box assembly design scheme and carbon fiber reinforced composite material layup design optimization method proposed in this paper is demonstrated.